The Development of Web Based Pregnancy Medical Checkup System (PregMedSyst) - Rosli, Nuriman Nadira; Fuad, Norfaiza (Evolution in Electrical and Electronic Engineering, 2023)
This project was carried out to develop a web-based pregnancy medical checkup system that allows patients to schedule their medical appointments online. This web-based system includes patient registration and storing their information in the system. The software can assign a unique id to each patient and store their personal information. A username and password are required to access the system, it is only accessible by an administrator. The data can be retrieved easily and the interface is very easy to use. The data is well protected for personal use.